The Effect of Sharia Stock Index Inclusion On ESG Disclosure: An Analysis of The Moderating Role of Company Size - Wulandari, Renny; Suhardianto, Novrys; Rahmiati, Alfa (Journal of Ecohumanism, 2025)
This study aimed to analyse the influence of the status of companies listed on a sharia stock index on their level of environmental, social, and governance (ESG) disclosure and analyse how the influence of company size on this effect. Theoretically, sharia-indexed companies are expected to have a better level of ESG disclosure. Using a sample of 365 observations of companies listed on the Jakarta Islamic Index (JII) in the period 2016–2023, the results showing that sharia-indexed companies disclose significantly more information related to economic, social, and governance aspects than companies that are not sharia-indexed. In addition, test results show that companies listed on the Islamic stock index tend to be consistent in social disclosure, regardless of their size. The findings also suggest that the Islamic stock index inclusion will have a weaker role in ESG disclosure as company size increases. This study contributes evidence that companies listed on an Islamic stock index make use of social disclosure as a tool to strengthen their reputation. It also has implications for regulators and capital market authorities, encouraging more balanced disclosure across all ESG dimensions, particularly the social and governance aspects, as larger company size poses higher challenges.